2022
DOI: 10.15244/pjoes/155963
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of Clay-Pyrite of Coal-Bearing Formation in the Endemic Fluorosis Area of Southwest China

Abstract: It is common practice to use clay for coal-burning in fluorosis areas on the border of Yunnan, Guizhou, where coal-bearing strata is widely outcropped, and clay for coal-burning is usually considered to be collected from efflorescent clay in coal-bearing strata by some scholars. However, the relevant chemical properties of the clay, the mechanism that causes the fluorosis are not clear and the chemical forms of fluorine species present during transfer from the clay to the human body remain unclear. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been shown that the weathering of clay-pyrite in coal produces HSO 4 − and sulfate, which further promote the release of fluoride from the clay. 35 These may be the root cause of the high concentration of fluoride, sulfate and acid in the surface soil of the northern Helan Mountains, resulting in fluorosis in sheep in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the weathering of clay-pyrite in coal produces HSO 4 − and sulfate, which further promote the release of fluoride from the clay. 35 These may be the root cause of the high concentration of fluoride, sulfate and acid in the surface soil of the northern Helan Mountains, resulting in fluorosis in sheep in this area.…”
Section: Resultsmentioning
confidence: 99%
“…− and sulfate, which further promote the release of uoride from the clay. 35 These may be the root cause of the high concentration of uoride, sulfate and acid in the surface soil of ) in acidic topsoil.…”
Section: Discussionmentioning
confidence: 99%